KERAGAMAN IDENTITAS BUDAYA PADA NISAN DI KOMPLEKS MAKAM DAMPANG MARANA’ KABUPATEN MAROS - Nazar, Riska Faradilla; Duli, Akin; Rosmawati; Muda, Khadijah Tahir (JURNAL ILMU BUDAYA, 2024)
In addition to functioning as a sign in Islamic tombs, tombstones can also be a feature that reflects a certain culture. This research was conducted at the Dampang Marana Tomb Complex, Lau District, Maros Regency. The aims to describe some of the diversity of cultural identities in the use of tombstones in the tomb complex. The research questions raised are how the types of tombstones used and how the cultural identity associated with the use of these tombstones. The explanation of the diversity of cultural identities in the Dampang Marana tomb complex provides information that at least there has been socio-cultural interaction between the local community living around the former power of Dampang Marana and outside culture. The research method is data collection in the form of literature study and field survey.  In the analysis step, comparative analysis and morphological analysis will be carried out.